Creation of Concentrates Using Oxidised Iron Ore Tailings by Transformation of their Magnetic Characteristacs and Subsequent Magnetic Separation - Ponomarenko, O.M.; Brik, A.B.; Dudchenko, N.O. (Science and Innovation, 2024)
Technological parameters of concentrated ores obtained using the designed and the conventional methods of beneficiation have been determined. The parameters of concentrated ores obtained by the proposed method have been established to be higher than that of those obtained by the conventional approaches. Iron density in the concentrated ores is 70.6 and 65.42%, respectively, with iron loss in the tails being 2.9 and 22.02%, respectively.